Impuestos, Tasas y Contribuciones en el presupuesto del GAD Municipal de Vinces - Carranza Espinoza, Melba Roxana (2018)
The Municipal Autonomous Decentralized Government of Vinces in a Public entity, with administrative-financial autonomy in charge of planning, managing and executing its own resources in order to solve each one the needs required by the communities in question to public works, basic services among others , exercising the capacities and competences attributed by COOTAD in complementarity with the Constitution that promotes territorial development and the change to good living. The present case study was developed according to the sub-line of FINANCIAL MANAGEMENT AND SOCIAL COMMITMENT with the theme: Taxes, Fees and Contributions in the Budget of the Municipal GAD of the Canton of Vinces, applying as a method the descriptive research (Sampieri, 2014) and as Information collection instrument was used interviews that were made to the Financial Department, in order to know what drawbacks are presented in the collections corresponding to the first group of current income or Self-management. Where will be analyzed the accounts that have less participation in question to collection within the periods 2016 and 2017. In order to know more about this topic, the field research technique was used, through the application of observation, interviews with the accounting assistants, information was obtained that would provide a broader knowledge on the subject addressed and at the same time it could be deduced that they are taking place in the collections of Taxes, Fees and Contributions, considering that these items are part of the budget line of the GADM of Vinces. 3 The Constitution of the Republic of Ecuador establishes principles of equity, territorial sustainability, and equality, promoting a mechanism for the development and strengthening of Decentralized Autonomous Governments in the distribution of public revenues, with the sole purpose of guaranteeing territorial development. In accordance with COOTAD, there are provisions that reduce the organizational structure of sectional governments and reduce administrative procedures with perspectives towards territorial change. (Batallan, 2013) On the other hand, the decentralization process, according to the territorial plan, seeks to insert development strategies creating participatory cultures that generate changes and institutional strengthening of the GAD of the country. (COOTAD, 2017). According to (Muñoz, 2015), he mentions that Decentralization has the action of organizing, directing and administering powers of the different governments and in this way satisfying the basic needs that are part of the population's sustainability and development. According to the newspaper, (EL TELEGRAFO, 2015) "73% of the income of the municipalities of Ecuador comes from the transfers delivered by the Central Government and with a minimum percentage of 21% is the result of the income of these GAD". This data shows that the GADM depend on transfers from the Central Government for the execution of their projects or programs to be executed. The municipal GAD of Vinces collects taxes, fees and contributions that are taxes regulated by ordinances according to the legal framework of COOTAD, and there are also ordinances made according to municipal activity, without this going against a legal rule. These ordinances are carried out by the municipal council and once approved, the mayor will verify the legality of the process and, therefore, that it will be 4 find according to the Constitution. The publication of the approved ordinance should make known about the new decision-making act, and its dissemination will be made by the media, either by written press or radio or television advertising, so that it is known to the public. The GADM of Vinces presents the lack of tax payments by taxpayers, this causes that each year a high debt index is generated that affects the income of the budget. The possible cause that would be taking place is that there are no procedures that counteract the problem and that this in turn contributes to the fact that the high figures of accounts receivable each year do not increase.